Self-reported patterns of impairments in mentalization, attachment, and psychopathology among clinically referred adolescents with and without borderline personality pathology - Bo, Sune (Borderline Personal Disord Emot Dysregul, 2017)
BACKGROUND: Previous research, which primarily focused on adult samples, suggests that individuals with borderline personality disorder (BPD) display high levels of psychopathology, dysfunctional mentalization and problematic attachment to others. The current study investigated whether impairments in mentalization, attachment, and psychopathology are more severe in outpatient adolescents with BPD than in a clinical comparison group. METHODS: Consecutive referrals to a child and adolescent psychiatric clinic were clinically assessed with a battery of self-report instruments to assess mentalization, attachment, and psychopathology. Specifically, in regard to BPD a self-report questionnaire was employed to decide if patients were classified into the BPD or the clinical comparison group. The main outcome variables of adolescents with a primary diagnosis of BPD were then compared with those of a clinical comparison group comprising patients receiving psychiatric diagnoses other than BPD. RESULTS: Relative to the clinical group without BPD, and after controlling for sociodemographic variables, the BPD group displayed poorer mentalizing abilities, more problematic attachments to parents and peers, and higher self-reported levels of psychopathology. CONCLUSIONS: The results of this study suggest that BPD is a severe mental condition in adolescents and is characterized by poor mentalizing abilities, attachment problems and high levels of psychopathology compared to adolescents with psychiatric disorders other than BPD. Hence, clinicians should consider BPD when conducting diagnostic assessments, and evidence-based treatments for this vulnerable group should be developed.